Electronic media and its impact on creating violence and hatred in Islamic societies - Ihsan Nasser Hussein Al-Zubaidi, Asst. Lect.Dr.; Muhammad Kazem Abdullah, Asst. Prof. Dr. (lark, 2024)
The world today is witnessing developments in the media, which dominates all areas of life, social, cultural, and intellectual, and has led to changing some concepts and consolidating other concepts, which may be true or false. The media Electronic technology depends on modern technology and has appeared in recent decades and has become the dominant hand among other media. It has prevailed and spread, and has become a great force of influence. In addition to what was mentioned, it has been characterized by ease of use and low costs, in addition to the infinite diversity of content. All of this makes the person active and strongly involved. While he stays Behind the scenes without knowing his identity, therefore, some media outlets played a negative role in forming a false image of Islam and strengthening the view of contempt towards this religion by portraying it with violence and terrorism, thus creating an idea in people’s minds that the relationship between Islam and terrorism is a close relationship, and the relationship of coexistence between the media can be explained Violence and hatred are based on the fact that the media sees these horrific incidents as fertile material and a media scoop that proves the status of these media outlets and pushes them into the ranks of media that can be relied upon as a source. For information, and as a form of media marketing and promotion, the reality is that we cannot ignore the role that the media plays in fueling violence, terrorism and extremism or supporting them through terrorists exploiting it to market their goals. And their purposes, and employing them to mislead the security services, and trying to control public opinion by publishing the terrorist operations that they carry out, given that the media campaigns that cover these operations help to achieve and complete their goals. They see in the media coverage of their crimes an important criterion in measuring the extent of the success of their terrorist act to the point of Some of them view a terrorist act that is not accompanied by media coverage as a failure. Directed media discourse is one of the most dangerous tools for misleading the public in all its categories. The issue of psychological and media warfare in any crisis or war is considered one of the most dangerous tools used in fighting the opponent, and it relies on the principle of paralyzing the recipient’s awareness to believe the information presented, leading to his psychological defeat, as it is taken It is a platform through which it exaggerates facts, falsifies images, and conveys events contrary to what is happening on the ground.